The Role of Body Adiposity Index in Determining Body Fat Percentage in Colombian Adults with Overweight or Obesity - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2017)
The aim of this study is to investigate the accuracy of body adiposity index (BAI) as a convenient tool for assessing body fat percentage (BF%) in a sample of adults with overweight/obesity using bioelectrical impedance analysis (BIA). The study population was composed of 96 volunteers (60% female, mean age 40.6 ± 7.5 years old). Anthropometric characteristics (body mass index, height, waist-to-height ratio, hip and waist circumference), socioeconomic status, and diet were assessed, and BF% was measured by BIA-BF% and by BAIBF%. Pearson’s correlation coefficient was used to evaluate the correlation between BAI-BF% and BF% assessed by BIA-BF%, while controlling for potential confounders. The concordance between the BF% measured by both methods was obtained with a paired sample t-test, Lin’s concordance correlation coefficient, and Bland-Altman plot analysis. Overall, the correlation between BF% obtained by BIA-BF% and estimated by BAI-BF% was r = 0.885, p < 0.001, after adjusting for potential confounders (age, socioeconomic status, and diet). Lin’s concordance correlation coefficient was moderate in both sexes. In the men, the paired t-test showed a significant mean difference in BF% between the methods (-5.6 (95%CI -6.4 to -4.8); p < 0.001). In the women, these differences were (-3.6 (95%CI -4.7 to -2.5); p < 0.001). Overall, the bias of the BAI-BF% was -4.8 ± 3.2 BF%; p < 0.001), indicating that the BAI-BF% method significantly underestimated the BF% in comparison with the reference method. In adults with overweight/obesity, the BAI presents low agreement with BF% measured by BIA-BF%; therefore, we conclude that BIA-BF% is not accurate in either sex when body fat percentage levels are low or high. Further studies are necessary to confirm our findings in different ethnic groups. © 2017 by the authors. Licensee MDPI, Basel, Switzerland.